Anatomical and Palynological study of Ricinus communisL.from Euphorbiaceaein Iraq - AL-Hadeethi, Muazaz Azeez; AL-Anbari, Aseel Kadem; Shlash, Hisham Majeed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
The anatomical study showed the epidermis leaves of Ricinus communis L.glabrous and withparacytic pattern, also the midrib of leavescomposedfrom a pyramidal shapearea with a circular tip like ascamel humpfrom the upper side consisting of supported collenchyma tissue, and the cross section of leaf petiole formed as an ovate shape as for the cross section of stem was a circular, also observed many druces crystaland aleuron grains that are spread in the cortex area. Pollen grain appeared under a scanning electron microscope that tricolporate, either the surface pattern was reticulate and the shape of pollen grain prolate spheroidal to subprolate